Distribution of Biochar Technology as an organic planting medium and optimal biochar dose for Abelmoschus Esculentus l. Moench growth and production - Yuniwati, Eny Dyah; Prasetya, Istiyono Kirno; Rahayu, Yekti Sri; Q, Qomarudin; Arshad, Imran (CV. Bimbingan Belajar Assyfa, 2023)
Okra is a healthy vegetable and medication. Growing okra on an organic medium and adding charcoal may boost output. Okra plant growth metrics and yields will be examined about the organic growing medium and biochar dose. The study was place in March 2021 at Sekarpuro Village, Pakis District, Malang Regency. This study employed a factorial Randomised Block Design (RAK) with two factors: Organic Planting Media and Biochar dose. Plant height (cm), number of leaves (strands), number of crop fruits (fruit), fruit weight per plant (grammes), fruit diameter, length, and bar weight are observation metrics—analysis of variance using ANOVA and BNT 5% difference test. The study found that 7.5 tons/ha of manure and 10 tons/ha of coconut fibre biochar naturally increased okra plant growth and output. Fruit and stem weights also varied with planting medium and charcoal. The finding is that organic growing medium treatment and biochar dose affect okra plant development.